2014
DOI: 10.1111/gfl.12122
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and hydrochemical properties of deep sedimentary reservoirs of the Upper Rhine Graben, Europe

Abstract: Hydraulic and hydrochemical data from several hundred wells mostly drilled by the oil and gas industry within the four deep carbonate and siliciclastic reservoirs of the Upper Rhine Graben area in France and Germany have been compiled, examined, validated and analysed with the aim to characterize fluids and reservoir properties. Due to enhanced temperatures in the subsurface of the Upper Rhine Graben, this study on hydraulic and hydrochemical properties has been motivated by an increasing interest in deep hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 51 publications
2
51
1
1
Order By: Relevance
“…Since the unconformities that define the basic lithostratigraphic units of the Buntsandstein in the northern Germanic Basin are not clearly documented in the study area, distinction between the different units is difficult (Bourquin et al 2006;Dachroth 1985;Feist-Burkhardt et al 2008;Hagdorn and Nitsch 2009;Szurlies 2007). Further complications are introduced by the varying Buntsandstein thicknesses; they vary from about 60 m in the south of the graben to approximately 500 m around Karlsruhe, but further northward the thickness decreases again to about 300 m (Boigk and Schöneich 1970;Stober and Bucher 2014). Additionally, the Buntsandstein can be found at different depths, ranging from about 1000 m below the land surface, down to 4000 m near Karlsruhe.…”
Section: Regional Geology and Geothermal Settingmentioning
confidence: 95%
See 1 more Smart Citation
“…Since the unconformities that define the basic lithostratigraphic units of the Buntsandstein in the northern Germanic Basin are not clearly documented in the study area, distinction between the different units is difficult (Bourquin et al 2006;Dachroth 1985;Feist-Burkhardt et al 2008;Hagdorn and Nitsch 2009;Szurlies 2007). Further complications are introduced by the varying Buntsandstein thicknesses; they vary from about 60 m in the south of the graben to approximately 500 m around Karlsruhe, but further northward the thickness decreases again to about 300 m (Boigk and Schöneich 1970;Stober and Bucher 2014). Additionally, the Buntsandstein can be found at different depths, ranging from about 1000 m below the land surface, down to 4000 m near Karlsruhe.…”
Section: Regional Geology and Geothermal Settingmentioning
confidence: 95%
“…Backhaus 1974;Hagdorn and Nitsch 2009;Richter-Bernburg 1974). Within the URG, the regional geothermal gradient is elevated to 45-50 °C km -1 , with local hot spots that have temperature gradients of up to 100 °C km −1 and make the URG a prime target for geothermal exploration in Germany (Schellschmidt and Clauser 1996;Stober and Bucher 2014). This positive temperature anomaly is commonly explained by a raised Moho due to the graben formation (Brun et al 1992) or by advective fluid flow (Schellschmidt and Clauser 1996;Pribnow and Schellschmidt 2000).…”
Section: Regional Geology and Geothermal Settingmentioning
confidence: 99%
“…The average geothermal gradient throughout the URG is ca 35-45 °C/km with high heat flow evident from numerous hot springs. Hydrogeological properties throughout the URG are highly complicated 10 ; however, the average groundwater yield rate as measured around geothermal sites and at a depth of ca 2 km is approximately 0.1 L/s. 11 An average 5 MW low-enthalpy geothermal plant in the URG produces from reservoir temperatures of about 130 °C at an average depth of 3.5-4.5 km and production flow rates of 40-130 L/s.…”
Section: Low-enthalpy Geothermal Energymentioning
confidence: 99%
“…Few studies, especially laboratory studies that offer values of porosity and permeability, have targeted the overlying Permo-Triassic sedimentary units (e.g. Haffen et al 2013;Stober and Bucher 2015;Vidal et al 2015;Griffiths et al 2016). For example, Haffen et al (2013) estimated the permeability of the Buntsandstein sandstones of EPS-1 using a portable TinyPerm II permeameter and found that their permeability ranges from 10 −15 to 10 −13 m 2 .…”
Section: Introductionmentioning
confidence: 99%